Community Operational Research
VIII, 366 p.
Keywords: Community Operational Research: OR and Systems Thinking for Community Development sets out the current concerns of Community Operational Research (Community OR for short) and explores new possibilities for its continued development. Leading Community OR writers, with international reputations in operational research and systems thinking, have contributed chapters that illuminate different aspects of Community OR theory and practice. There is a focus on the value of systems approaches, and other significant perspectives are also represented. The result is a rich mix of theories, methodologies and case studies that will be a significant resource for both practitioners and academics engaged in community development.